High consistency between characteristics of primary intraductal breast cancer and subtype of subsequent ipsilateral invasive cancer. Issue 1 (February 2020) - Gennaro, Massimiliano; Meneghini, Elisabetta; Baili, Paolo; Bravaccini, Sara; Curcio, Annalisa; De Santis, Maria Carmen; Lozza, Laura; Listorti, Chiara; Di Cosimo, Serena; Sant, Milena; Folli, Secondo
Background: Ductal carcinoma in situ (DCIS) is considered a morphologic precursor of invasive cancer and is often treated with adjuvant whole-breast irradiation and endocrine therapy, as if it were an invasive cancer. Our aim was to provide further support for treatment de-escalation or enrollment of such patients in active surveillance trials. Methods: We retrospectively analyzed data on patients with conservatively treated primary DCIS subsequently diagnosed with ipsilateral invasive breast cancer (IBC) at 2 comprehensive breast cancer centers. From their merged databases, we identified 50 cases with full details on tumor grade, hormone receptor expression, and HER2 amplification, for both the primary DCIS and the corresponding IBC, and we assessed the similarities and differences between the two. Results: Distributions of hormone receptors were similar in primary DCIS and IBC, while high-grade and HER2-positive status was less common in IBC than in primary DCIS. The positivity for estrogen receptors (ER) and well-differentiated or moderately differentiated morphology in the primary DCIS persisted in 90% of the matching IBC. Changes in progesterone receptor expression were slightly more common than those in ER expression. Overall consistency for the luminal-like receptors subtype was found in 90% of cases. Conclusion: The high consistency between the features of primary DCIS and those of subsequent IBC (in the rare but not negligible cases of local failure) should be borne in mind when considering the therapeutic options. Treatment de-escalation and accrual of patients for active surveillance trials could be appropriate for luminal-like precursors.